Citation analysis of 10-year Islamic economic research papers indexed in dimensions.ai - Muhammad Muhajir Aminy; Restu Fahdiansyah; Shofia Mauizotun Hasanah (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2021)
The main objective of this study is to analyze cited papers in terms of the most cited author, journal, article, and institution. All documents are listed on dimensions.ai as the source of papers and containing the keyword “Islamic economics” in the title or abstract of the articles. The research method used in this study is citation analysis. The publication period is 10 years, starting from 2012 to 2021. This study showed that only 264 (19.32%) of 1,366 published articles were cited at least once by other documents during the observation period. The majority of these items came from Indonesia, with a total of 120 documents (45.4%). The most cited author is Hafas Furqani with 13 articles (4.9%), the most cited journal is Jurnal Ekonomi Syariah (JES) with a total of 32 articles (12.1%), the most cited article is a paper titled "Corporate social responsibility, waqf system, and zakat system as faith-based model for poverty reduction" with its 33 citations, and the most cited institution is Airlangga University in Indonesia with a total of 18 articles (6.8%). This research also provided a finding that 25 institutions and organizations cite one another in their published articles.